Сага о шпионской любви: [роман] / И. Атаманенко - Атаманенко Игорь Григорьевич (Остросюжет, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54007 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 92 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4